Pancasila As a Rechtsidee and Natural Resource Management Dilemma in the Global Era - Suteki, Suteki (Law Research Review Quarterly, 2016)
Indonesia's natural resources (SDA) are clearly regulated through the 1945 Constitution of the Republic of Indonesia and various related laws and regulations. The management of natural resources must be based on Indonesia's basic constitution and also the values of Pancasila. But the fact is, many cases show that the management of natural resources has not been fulfilled as mandated by the 1945 Constitution of the Republic of Indonesia.